2022
DOI: 10.3389/fimmu.2022.853403
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Characteristics of T-Cell Receptor Repertoire Between Essential Hypertension and Aldosterone-Producing Adenoma

Abstract: Aldosterone-producing adenoma (APA) is a benign adrenal tumor that results in persistent hyperaldosteronism. As one major subtype of primary aldosteronism, APA leads to secondary hypertension that is associated with immune dysregulation. However, how the adaptive immune system, particularly the T-cell population, is altered in APA patients remains largely unknown. Here, we performed TCR sequencing to characterize the TCR repertoire between two age-matched groups of patients: one with APA and the other one with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Confronting the issues they have artfully delineated, we duly acknowledge the significance of nutritional variables, notably caffeine and salt intake, and their potential repercussions on the renin-angiotensin-aldosterone system (RAAS) [2]. We wholeheartedly concur with their recommendation to incorporate these variables into our future analytical framework.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Confronting the issues they have artfully delineated, we duly acknowledge the significance of nutritional variables, notably caffeine and salt intake, and their potential repercussions on the renin-angiotensin-aldosterone system (RAAS) [2]. We wholeheartedly concur with their recommendation to incorporate these variables into our future analytical framework.…”
mentioning
confidence: 81%
“…While the study accounted for effects of hypertensive medications on the renin-angiotensin-aldosterone system (RAAS) by discontinuing these medications before primary aldosteronism diagnosis, some nutritional factors that affect RAAS that were not considered. Robertson et al [2] demonstrated that acute caffeine consumption increased serum renin levels significantly, which would cause an increase in downstream plasma aldosterone concentrations. In addition, a large body of research demonstrated that salt intake has an inverse relationship with renin production/RAAS activation, though the exact mechanism remains unknown [3].…”
mentioning
confidence: 99%
“…As a further example, it has been shown that patients with EH or hypertension due to secondary causes like aldosterone-producing adenoma display a different type of TCR repertoire. 15 Ma et al 13 found a positive correlation between reduced T cell clone diversity and the number of antihypertensive drugs taken. This information could be related to the fact that patients with enhanced immune activation might have severe hypertension and, consequently, assume more drugs.…”
Section: See Related Article Pp 2318-2329mentioning
confidence: 99%
“…As a further example, it has been shown that patients with EH or hypertension due to secondary causes like aldosterone-producing adenoma display a different type of TCR repertoire. 15…”
mentioning
confidence: 99%